2016
DOI: 10.1155/2016/4968365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modification with Various Epoxide Compounds on Mechanical, Thermal, and Coating Properties of Epoxy Resin

Abstract: Epoxy resin (ER) was modified with four different epoxide compounds, 4,5-epoxy-4-methyl-pentane-2-on (EMP), 3-phenyl-1,2epoxypropane (PhEP), 1-chloro-2,3-epoxy-5-(chloromethyl)-5-hexene (CEH), and a fatty acid glycidyl ester (FAGE), to improve its chemical and physical properties. The effects of the addition and amount of these modifiers on mechanical, thermal, and coating properties were investigated. Atomic force microscopy was used to observe the changes obtained with the modification. The influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
5
11
0
1
Order By: Relevance
“…Results indicated that the drying time of the epoxy coatings was decreased with the addition of metal powder in the order T 0 > T 5 > T 10 . These results are in agreement with other researchers who had reported that the incorporation of the different metallic fillers on a micro-and a nanoscale had decreased the curing time of the coating [35][36][37]. PVC is an essential tool for coatings and is responsible for the gloss and hiding power.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Results indicated that the drying time of the epoxy coatings was decreased with the addition of metal powder in the order T 0 > T 5 > T 10 . These results are in agreement with other researchers who had reported that the incorporation of the different metallic fillers on a micro-and a nanoscale had decreased the curing time of the coating [35][36][37]. PVC is an essential tool for coatings and is responsible for the gloss and hiding power.…”
Section: Resultssupporting
confidence: 92%
“…Dry film thickness, % pigment volume concentration (PVC), % volume of Ti metal powder, drying time, pencil hardness, and adhesion loss of T 0 , T 5 , and T 10 coatings were measured. Earlier work has shown that drying comprises many time-consuming physical and chemical reactions, including polymerization, evaporation of the organic solvent, and oxidation reaction of the resin [34][35][36][37]. It is influenced by variables like light, temperature, nature of the substrate, the thickness of the film, and air movement [34,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxy polymer resin has outstanding characteristics, such as extraordinary strength, limited shrinkage, & excellent heat and chemical resistance. Because of its unique properties, epoxy is used in many applications as coats, bonding agents, and matrix constituents for composites [1]. Cured epoxy systems have shown minute endurance to crack instigation and propagation & poor fracture toughness, in its applications [2].…”
Section: Epoxy-nanoclay Composites (Encs)mentioning
confidence: 99%
“…4. Температура стеклования эпоксидных композиций, определенная термомеханическим методом тературным данным, полиненасыщенные кислоты, такие как линоленовая, содержащая три двойные связи, и линолевая с двумя двойными связями [18].…”
Section: табл 3 жизнеспособность модифицированных эпоксидных композunclassified